An Overview of Semisolid Processing of Aluminium Alloys. (28th January 2013) - Salleh, M. S.; Omar, M. Z.; Syarif, J.; Mohammed, M. N.
Abstract : Semisolid metal processing (SSM) or thixoforming is a new technology that offers several advantages over liquid processing and solid processing. This process utilizes semisolid behavior as well as reduces macrosegregation, porosity, and forming forces during shaping process. A lot of research work has been carried out by various researchers in order to exploit the potential of this process to produce different products especially for automotive industry. This paper will summarise the rheological behavior of aluminium alloys in semisolid slurries, thixoformability of modified aluminium alloys, the effect of feedstock production method on mechanical properties, and the importance of developing low-cost raw materials for semisolid processing.